2021
DOI: 10.2337/dc20-2014
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exenatide Once Weekly on Carotid Atherosclerosis in Individuals With Type 2 Diabetes: An 18-Month Randomized Placebo-Controlled Study

Abstract: OBJECTIVE Glucagon-like peptide 1 receptor agonists (GLP-1RAs) improved multiple proatherogenic risk factors and reduced cardiovascular events in recent clinical trials, suggesting that they may slow progression of atherosclerosis. We tested whether exenatide once weekly reduces carotid plaque progression in individuals with type 2 diabetes. RESEARCH DESIGN AND METHODS In a double-blind, pragmatic trial, 163 participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Although human studies examining atherosclerosis remission with GLP-1RAs are limited, open-label observational studies of several hundred people with T2D treated with liraglutide ( 45 ) or exenatide once weekly ( 46 ) detected reduction in carotid intima media thickness, as assessed by carotid Doppler examination. In contrast, no change in carotid artery plaque volume or composition, as assessed by carotid MRI, was detected in 631 people with T2D randomized to receive placebo or exenatide once weekly for 18 months ( 47 ). Hence, it seems premature, based on the available evidence, to conclude that GLP-1RAs are uniformly capable of inducing atherosclerosis regression.…”
Section: Discussionmentioning
confidence: 99%
“…Although human studies examining atherosclerosis remission with GLP-1RAs are limited, open-label observational studies of several hundred people with T2D treated with liraglutide ( 45 ) or exenatide once weekly ( 46 ) detected reduction in carotid intima media thickness, as assessed by carotid Doppler examination. In contrast, no change in carotid artery plaque volume or composition, as assessed by carotid MRI, was detected in 631 people with T2D randomized to receive placebo or exenatide once weekly for 18 months ( 47 ). Hence, it seems premature, based on the available evidence, to conclude that GLP-1RAs are uniformly capable of inducing atherosclerosis regression.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cIMT reduction has been proven for liraglutide [17]. However, conflicting results on the atherosclerosis process (cIMT reduction, plaque volume and composition) were published for exenatide, as expected [11][12][13].…”
Section: Discussionmentioning
confidence: 86%
“…Nevertheless, the cardiovascular protective mechanisms of GLP-1 receptor agonists are still poorly understood, even though some have been proposed, such as anti-inflammatory properties, improvement of endothelial dysfunction and reduction of myocardial ischaemia injury; however, not all GLP-1 receptor agonists have proven to have cardio-renal protective actions [10]. Those with a proven ability to reduce major adverse cardiovascular events (MACE) are liraglutide, dulaglutide, albiglutide and subcutaneous semaglutide; in contrast, oral semaglutide was found to show only a trend towards MACE reduction, but this effect was not statistically significant as the cardiovascular noninferiority study lasted \ 2 years [11][12][13]. Further studies are ongoing that will show whether treatment with oral semaglutide could reach the same beneficial effect on MACE as its injectable counterpart [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] However, research on the use of GLP-1RAs has shown an association of such treatment with an increase in heart rate. [6][7][8][9] Heart rate is directly inversely associated with survival in the general population and in individuals with cardiovascular conditions. 10,11 For every 5-bpm increase in heart rate in patients with coronary artery disease and left ventricular dysfunction, the risk of cardiovascular mortality and hospital admission for worsening heart failure increased by 16%.…”
Section: Introductionmentioning
confidence: 99%